If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2m + -7n)(2m + -3n) = 0 Multiply (2m + -7n) * (2m + -3n) (2m * (2m + -3n) + -7n * (2m + -3n)) = 0 ((2m * 2m + -3n * 2m) + -7n * (2m + -3n)) = 0 Reorder the terms: ((-6mn + 4m2) + -7n * (2m + -3n)) = 0 ((-6mn + 4m2) + -7n * (2m + -3n)) = 0 (-6mn + 4m2 + (2m * -7n + -3n * -7n)) = 0 (-6mn + 4m2 + (-14mn + 21n2)) = 0 Reorder the terms: (-6mn + -14mn + 4m2 + 21n2) = 0 Combine like terms: -6mn + -14mn = -20mn (-20mn + 4m2 + 21n2) = 0 Solving -20mn + 4m2 + 21n2 = 0 Solving for variable 'm'. Factor a trinomial. (2m + -7n)(2m + -3n) = 0Subproblem 1
Set the factor '(2m + -7n)' equal to zero and attempt to solve: Simplifying 2m + -7n = 0 Solving 2m + -7n = 0 Move all terms containing m to the left, all other terms to the right. Add '7n' to each side of the equation. 2m + -7n + 7n = 0 + 7n Combine like terms: -7n + 7n = 0 2m + 0 = 0 + 7n 2m = 0 + 7n Remove the zero: 2m = 7n Divide each side by '2'. m = 3.5n Simplifying m = 3.5nSubproblem 2
Set the factor '(2m + -3n)' equal to zero and attempt to solve: Simplifying 2m + -3n = 0 Solving 2m + -3n = 0 Move all terms containing m to the left, all other terms to the right. Add '3n' to each side of the equation. 2m + -3n + 3n = 0 + 3n Combine like terms: -3n + 3n = 0 2m + 0 = 0 + 3n 2m = 0 + 3n Remove the zero: 2m = 3n Divide each side by '2'. m = 1.5n Simplifying m = 1.5nSolution
m = {3.5n, 1.5n}
| -9(-2r-10s+3)= | | 2Inx-5Inx=6 | | 3x-1x+4x+13=180 | | 8(c-6)= | | (4x^2-6)(7x^2-7)= | | 5-3/2(6-2/3y) | | 13(x+5)= | | 3x+2=5x-18 | | y=3x^3-7x^2-14x+24 | | log5[5x/x-2]=2 | | 3b-5b=10 | | 3.25b-1.5=14.5 | | 3.25-1.5=14.5 | | 3(x-7)=63 | | Ln(x)=-90 | | 3(c-4)=3c-12 | | -6p+8+7p=12 | | 7r^2+10r-72=0 | | 2w=36+5w | | 7r^2+10-72=0 | | 3y+15x=-24 | | 100+10xlog=60 | | 3x-3x-4=4 | | 2t-S=2u | | 6y-48=8 | | 4x=-2x-8 | | -9-4(-11)= | | -11x+4=62 | | 2ln(x+1)=ln(x^2-1) | | 3y-7y=-3y+-19 | | 3x^2-33y=0 | | 3x+20+3y=180 |